Occasional nouns in the texts of Ukrainian postmodern prose (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2009)
The article presents standard and specific ways of word-formation of occasional nouns which function in the texts of Ukrainian postmodern prose. The producing of lexical occasionalisms is considered as one what enriches of language-expressing means of modern Ukrainian literature and therefore is interesting for many areas of linguistics for instance lexicology, stylistic, word building, theory of nomination and others.
Keywords: occasional noun; standard ways of word-formation; occasional ways of word-formation; occasionalisms